Examining the Relationship between Severity of Thrombocytopenia and the Pattern of Malaria: A Hospital-Based Study - Saeed, Javeria Rauf (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To determine the association between the severity of thrombocytopenia and the pattern of malaria. METHODOLOGY This descriptive cross-sectional study included 194 patients who tested positive for malarial parasites on peripheral smear examination. The study comprised smear-positive malaria cases, both males and females, who were Pakistani nationals aged between 8 and 50. Exclusion criteria were individuals with dengue, typhoid, immunocompromised status, liver disease, and pregnancy. Data were recorded for age, gender, the pattern of malaria (Plasmodium (P). vivax, P. falciparum, or mixed), and type of thrombocytopenia (mild, moderate, and severe). The association between the severity of thrombocytopenia and the pattern of malaria was determined using a chi-square test, with the analysis stratified by gender. RESULTS The mean age of the participants was 28.58±11.70 years, with 114 (58.76%) being male. The lowest platelet count (64,627 ± 43,062) was found in cases of falciparum malaria, while the highest mean platelet count was found in cases of vivax malaria (130,919 ± 107,723), and this difference was statistically significant (p=0.004). The most common occurrence of severe thrombocytopenia was in falciparum malaria cases (n=11, 42.31%), and the difference was statistically significant (p=0.024). CONCLUSION Falciparum malaria has the lowest mean platelet count and more severe thrombocytopenia than vivax and mixed type.